2012
DOI: 10.4049/jimmunol.1200324
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of Cell Adhesion Molecule Nectin-2/CD112 and Its Binding to Immune Receptor DNAM-1/CD226

Abstract: The nectin and nectin-like molecule (Necl) family includes important cell adhesion molecules (CAMs) characterized by their Ig-like nature. Such CAMs regulate a broad spectrum of cell–cell interactions, including the interaction between NK cells and cytotoxic T lymphocytes (CTLs) and their target cells. CAM members nectin-2 (CD112) and Necl-5 (CD155) are believed to form homodimers (for nectin-2) or heterodimers in their functions for cell adhesion, as well as to interact with immune costimulatory receptor DNAX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
42
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 69 publications
5
42
0
1
Order By: Relevance
“…However, it remains a possibility that the cis-interaction between IgV domains proposed on the basis of the nectin-1 structure could act as a regulatory mechanism to control the extent of transinteractions. In summary, on the basis of our structural and biochemical data, as well as previously reported data (16)(17)(18)(19), we believe that our nectin-2 dimer represents the biologically relevant homophilic transinteraction shown in Fig. 5.…”
Section: Heterophilic Interactionssupporting
confidence: 86%
“…However, it remains a possibility that the cis-interaction between IgV domains proposed on the basis of the nectin-1 structure could act as a regulatory mechanism to control the extent of transinteractions. In summary, on the basis of our structural and biochemical data, as well as previously reported data (16)(17)(18)(19), we believe that our nectin-2 dimer represents the biologically relevant homophilic transinteraction shown in Fig. 5.…”
Section: Heterophilic Interactionssupporting
confidence: 86%
“…SeMet Dare-PTX was prepared using a reported method (Blackburn et al, 1999;Chen et al, 2010;Garboczi et al, 1996). The purification procedures for native and SeMet Dare-PTX were performed in accordance with the method described in our previous reports (Chen et al, 2010;Liu et al, 2012). The Dare-PTX inclusion bodies were extracted, and Dare-PTX was renatured in refolding buffer.…”
Section: Protein Preparationmentioning
confidence: 99%
“…Structure determination was performed using the singlewavelength anomalous diffraction (SAD) method, as previously reported (Liu et al, 2012). Briefly, the expected heavy atoms were determined by SHELXD (Schneider and Sheldrick, 2002), and then initial phases were determined using Phaser (McCoy et al, 2007).…”
Section: Data Refinement and Structure Determinationmentioning
confidence: 99%
“…Nectin-2 is also a ligand of the activating natural killer (NK) cell receptor DNAX accessory molecule 1 (DNAM-1) (43,(89)(90)(91)(92). Work in PRV and HSV-2 showed that following cellular transfection with gD or viral infection, DNAM-1 was downregulated to prevent NK cell-mediated cytolysis of infected cells (93).…”
Section: Discussionmentioning
confidence: 99%